MATHEMATICAL ASSESSMENT ON DYNAMICS OF GOVERNMENT EXPENDITURES AND GROSS DOMESTIC PRODUCT PER CAPITA, IN ROMANIA AND EUROPEAN UNION - UZLAU, MARILENA CARMEN; MIHAILESCU, NICOLAE; ENE, CORINA MARIA; IONESCU, CONSTANTIN AURELIAN; PASCHIA, LILIANA; GUDANESCU NICOLAU, NICOLETA LUMINITA; STANESCU, SORINA GEANINA; COMAN, MIHAELA DENISA (Journal of the sciences and arts, 2021)
The research purpose represents the identification and mathematical definition of some models expressed by regression equations describing the GE per inhabitant according to the GDP per inhabitant. The study is customized at EU level and in seven states located in the Eastern-EU (RO, PL, GR, BG, SI, SK and HU) for the period 2009-2018. The research methodology is based on econometric modelling and testing of their viability. Relevant conclusions are also made regarding RO's position in the European Union in terms of government spending. The research provides useful information to substantiate micro and macroeconomic decisions designed to ensure a dynamic of GE’s sustainable growth on education, health, general public services, defense, public order and safety. Based on the developed econometric models, values of endogenous variables (GE per capita) can be estimated depending on the variants of predictable scenarios for the size of the GDP per capita.